Evaluasi penyimpanan obat di Puskesmas "X" Kabupaten Sleman - Novi Dwi Rugiarti; Atika Nurul Hidayati; Dian Medisa; Diesty Anita Nugraheni (Jurnal Ilmiah Farmasi, 2021)
AbstractBackground: Medicines storage is one of the stages in drug management, which plays an essential role in ensuring the quality and availability of drugs. Therefore, it is necessary to evaluate medicines storage by comparing the performance with the storage efficiency indicators.Objective: This study aimed to determine the efficiency of medicines storage in “X” Primary Healthcare, Sleman Regency.Methods: This research was an observational study during April-May 2020 in “X” Primary Healthcare. Data collection was carried out retrospectively. Data were analyzed based on drug efficiency indicators, including the percentage of expired drugs, the percentage of dead stock, and turnover ratio (TOR).Results: The results showed 2.45% expired drugs, 2.45% deadstock, and 5.2 times TOR. The most expired drugs were pipemidic acid 400 mg, nifedipine 10 mg, and carbamazepine 200 mg.Conclusion: The storage of medicines in "X" Primary Healthcare was not yet efficient.Keywords: Drug storage, efficiency, primary healthcare